1949
DOI: 10.1302/0301-620x.31b3.444
|View full text |Cite
|
Sign up to set email alerts
|

The Strength and Elasticity of Bone in Rats on a Rachitogenic Diet

Abstract: Since bone is primarily a supporting and protecting tissue it seems appropriate to investigate its properties in the same way that an engineer measures the characteristics of 444 THE JOURNAL OF BONE AND JOINT SURGERY

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

1956
1956
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…to a characteristic length. Contrary to this, interspecific scaling studies indicate that musculoskeletal tissue properties in mammals scale independently of body mass (Weir et al, 1949;Smith and Walmsley, 1959;Currey, 1979;Biewener, 1982;Pollock and Shadwick, 1994b;Medler, 2002). However, ontogenetically within a species, the current study suggests that material properties (Young's modulus) in some tendons do indeed appear to scale as predicted by dynamic similarity.…”
Section: Tendon Stiffness and Materials Propertiescontrasting
confidence: 57%
“…to a characteristic length. Contrary to this, interspecific scaling studies indicate that musculoskeletal tissue properties in mammals scale independently of body mass (Weir et al, 1949;Smith and Walmsley, 1959;Currey, 1979;Biewener, 1982;Pollock and Shadwick, 1994b;Medler, 2002). However, ontogenetically within a species, the current study suggests that material properties (Young's modulus) in some tendons do indeed appear to scale as predicted by dynamic similarity.…”
Section: Tendon Stiffness and Materials Propertiescontrasting
confidence: 57%
“…The same results were reported by Salomon & Volpin (1972) in growing rats on low calcium diet which gave lighter and thinner long bones and decreased bending strength of metatarsals with increasing deflection in bending. Weir et al (1949) found decrease of bending strength and stiffness and increase of deflection in rats on a rachitogenic diet even with supplement of vitamin D. They concluded that the effects were depending of, and correlated with, a corresponding decrease in ash volume.…”
Section: Experimental Osteoporosis -Osteopeniamentioning
confidence: 96%